Bacillus subtilis ccpA Gene Mutants Specifically Defective in Activation of Acetoin Biosynthesis - Turinsky, Andrew J. (American Society for Microbiology, 2000)
A large number of carbon source utilization pathways are repressed in Bacillus subtilis by the global regulator CcpA, which also acts as an activator of carbon excretion pathways during growth in media containing glucose. In this study, CcpA mutants defective in transcriptional activation of the alsSD operon, which is involved in acetoin biosynthesis, were identified. These mutants retained normal glucose repression of amyE, encoding α-amylase, and acsA, encoding acetyl-coenzyme A synthetase, and normal activation of ackA, which is involved in acetate excretion; in these ccpA mutants the CcpA functions of activation of the acetate and acetoin excretion pathways appear to be separated.